Online advertising and its impact on the purchasing behavior of Iraqi women"A survey study on a sample of women in southern Iraq" - Ammar Hamad Jabr (Thi Qar Arts Journal, 2025)
Aims this Research to detect exposure rate Women in southern Iraq For electronic advertising and knowledge of the means of communication used In this, monitoring the causes of exposure and knowing the forms and types Advertisements and the products they buy Under the influence of electronic advertisements and the extent of their reliance on advertising In the Get the information, And knowledge The impact of advertisements on their orientation and behavior They are Purchasing, and Monitoring influencing factors In this behavior and Knowledge of persuasive uses and Cognitive, emotional and behavioral effects of the exposure For electronic advertising, by way of Bana It was applied to a simple random sample of (300) women in the southern governorates of Iraq, and finished The study reached the following results: the high rates of exposure of the research sample to electronic advertisements through the use of mobile phones and tablets. Because it is providing them with ease and speed in obtaining products, while they prefer Researched Monitor competitive advertisements that compare products and their benefits, and provide guidance about the product. At unknown And Previously, which helps them acquire Necessities of life such as food and clothing and cosmetics, Their degree of dependence on advertisements is high. And influential in making the purchasing decision, while the research hypotheses were proven correct by the existence of a correlation between the extent of exposure Researched For electronic advertisements and the degree of their influence on their purchasing decision, and Between the extent of their exposure to electronic advertisements and the degree of their reliance on them to obtain information goods Which they are willing to buy, and the presence of statistical differences on the scale of cognitive, emotional and behavioral effects of exposure They are For advertisements and demographic variables "age and Profession and Economic level.